(10*6^n)/(2^(2n+1)*3^(n-1))упростить выражение ((с^4)/(6x^2 * y^(-5))^(-2) *((1)/(3)*c^2*x^3*y^(-2))^4      упростить выражение  

(10*6^n)/(2^(2n+1)*3^(n-1))упростить выражение ((с^4)/(6x^2 * y^(-5))^(-2) *((1)/(3)*c^2*x^3*y^(-2))^4      упростить выражение  
Гость
Ответ(ы) на вопрос:
Гость
1. [latex]\frac{10*6^n}{2^{2n+1}*3^{n-1}}=\frac{5*2^{n+1}*3^n}{2^{2n+1}*3^{n-1}}=[/latex][latex]5*2^{n+1-2n-1}*3^{n-n+1}=5*2^{-n}*3=\frac{15}{2^n}[/latex] 2. [latex](\frac{c^4}{(6x^2 * y^{-5})^{-2}} *(\frac{1}{3}*c^2*x^3*y^{-2})^4=\frac{36c^4x^4}{y^{10}}*\frac{c^8x^{12}}{81y^8}=\frac{4c^{12}x^{16}}{9y^{18}}[/latex] 
Не нашли ответ?
Ответить на вопрос
Похожие вопросы